Analisis PSAK No. 45 dalam penyajian Laporan Keuangan Organisasi Nirlaba Studi Kasus pada Rumah Sakit âXâ - Sutarti, Sutarti; Prayitno, Deni (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2007)
The target of this research is to analyze presentation of organizational financial statement of the organization (hospital). Analysis was conducted to find out whether the presentation of hospital financial statement is in accordance with Statement of Standard Financial Accounting (PSAK) Number 45. Result of the research indicated that Hospital âXâ has presented financial statement matching PSAK No. 45, that can be seen in its financial statement component consisting of : financial position report, activity report, cash flow statement, and note to the financial statement. Analysis result in this research indicated that there is some revision in the financial statement. Firstly, the presentation concerning the resource which the hospital has, like: unattached net asset, transient tied, and tied permanent which are grouped into equity which mirror in financial position report. Equity at profit organization/company respresents owner equity which consists of capital stock and retained earning, while at the non-profit organization like Hospital âXâ, its ownership is not based on the capital stock and retained earning. Secondly, the Hospital âXâ had better consider assessment and abolishment of stock. This includes the stock which has no transfer (dead stock) and the slow moving stock exceeding two years or worn are moved into the others asset or the stock will be abolished. Keywords : presentation of financial statement, applying of PSAK No. 45.